Antenatal and postnatal depression in Vietnam: A prospective cohort study - Chu, Khac Tan (Curtin University, 2021)
This thesis was part of a multi-center prospective-cohort study conducted in six hospitals in Vietnam. A total of 2030 pregnant women were recruited and interviewed face-to-face at 24-28 weeks of gestation, with four follow-up visits from discharge to six months postpartum. The aims of this thesis were to review the prevalence and major determinants of perinatal depression in Asia and to determine the prevalence of and factors associated with perinatal depressive symptoms among Vietnamese women.